Moving from traditional to Agile information systems development in a large organisation: two complementary models of organisational Agile implementation - De Souza, Jules Vincent (Curtin University, 2020)
This study investigated the key elements that shape the implementation of an Agile method in an organisation as it moves from a traditional to an Agile approach. The results reveal that organisational change is the key element. This study presents two complementary theoretical models (an integrated thematic model and a process model) which provides a comprehensive explanation of the change surrounding Agile implementation. It will assist organisations in developing strategies to manage the organisational change.